Images of men and women in the Dagestan language picture of the world (based on the Rutul language) - S.M. Makhmudova (Язык и текст, 2019)
The autochthonous Dagestan languages belong to an ergative typology, in which the entire language system is subordinated to the reflection of the semantics of the subject’s activity / passivity, his participation / non-participation in the event happening with him or around him, the subject’s influence on the object, the activity / passivity of which is also controlled by the subject. At the same time, the subject himself can take shape in different cases, expressing his role in what is happening or produced by the event itself. The whole system of declination of the Rutul language is subordinated to the expression of the semantics of the subject's activity, the main semantic component of which is the principle of anthropocentrism. The article discusses the features of the reflection of the people's thinking and their ideas about the world in language, which imprint not only on the linguistic picture of the world, but also on the structure of the language itself.